Analisis Kesadaran Hukum Warga Negara Dalam Pasal 27 Ayat 2 UU ITE Terhadap Tindak Pidana Perjudian - Putra, M.Adi Pratama (UNTIRTA CIVIC EDUCATION JOURNAL, 2024)
Technological advances have brought a significant impact in various aspects of life, including the emergence of the online gambling phenomenon that is increasingly rampant in Indonesia, especially in the West Jakarta region. This research aims to analyse public legal awareness of Article 27 Paragraph 2 of the Electronic Information and Transaction Act (UU ITE) in eradicating online gambling crimes. The research is carried out with a descriptive qualitative approach based on the philosophy of postpositivism, with researchers as the main instrument. The research location is focussed on Grogol Petamburan, West Jakarta, during the period from July to October 2024. Data is collected through interviews, direct observation, and analysis of legal documents, with data validity tested using triangulation techniques and sources. The results of the study show that the level of public legal awareness of Article 27 Paragraph 2 of the ITE Law is still low, while law enforcement faces various challenges, including limited resources and the complexity of technology used by online gamblers. This study also found that the successful implementation of Article 27 Paragraph 2 of the ITE Law is greatly influenced by the cooperation between the community, law enforcement officers, and the government in increasing legal awareness and supervision of online gambling activities. This research is expected to contribute to the prevention and handling of online gambling crimes in Indonesia.